Android-Based Remote Control Solar Power Plant Panels with Direct Current System Installation - Yusril Afandi; Jamaaluddin Jamaaluddin (Procedia of Engineering and Life Science, 2021)
Energy hot sun very overflow especially in area with climate tropical as indonesia that always exposed rays throughout years. This is a source energy that could on developed. on research aimed at to make it easier and knowing damage panel generator electric power sun more early so that soon get to do troubleshooting early before damage continue with use microcontroller NodeMCU right has been IOT designed component additional sensor INA219 gauge current, voltage, lux intensity light is snown software application BLYNK in smartphone. the results research is toll monitoring read high low battery and lamp. In the result measurement this will is snown menu application BLYNK that has been designed.